WELL building: Criteria for residential buildings in a developing country - Salma Husna, Zamani; Rahimi, A. Rahman; Liyana, Mohamed Yusof (Engineering Project and Production Management, 2023)
Health, well-being, and productivity are the main notions for WELL buildings. Although the WELL building standard does exist to follow when designing a building, the concepts and elements might differ between developed and developing counties and types of buildings. However, there is a lack of knowledge on WELL building concepts and elements in developing countries and residential buildings. Thus, this study uses Malaysia as a case study to investigate the elements that affect health, well-being, and productivity (i.e., WELL) for residential buildings in a developing country. First, semi-structured interviews with built environment industry professionals and individuals living in multi-story residential buildings were carried out. Then, the interview data were analyzed using the thematic analysis technique to generate concepts and elements of WELL for residential buildings in a developing country. The analysis identified nine WELL concepts for residential buildings: air, water, fire, fitness, comfort, mind, safety & security, community, and maintenance & management. Furthermore, the nine themes consist of 53 building elements. The findings suggest three additional new WELL concepts for residential buildings in a developing country: fire, safety & security, and maintenance & management. This is the first study that evaluates the element of WELL for residential buildings that contribute to the existing WELL building standard within the context of a developing country.